Improving soil health using tillage techniques to increase soil carbon sequestration - Leichty, Sarah, author; Cotrufo, Francesca, author; Stewart, Catherine, author (Colorado State University. Libraries, 2017)
Soil carbon sequestration is a strategy to mitigate greenhouse gas emissions while enhancing microbial processes and water retention. Agricultural practices that leave residue on the surface without tilling have been promoted to sequester more C. However, recent work shows a redistribution of C rather than an increase when the entire soil profile is measured. This project will determine if surface application or incorporation (10 cm) stabilizes more residue throughout the soil profile (100 cm) using carbon stable isotope-labeled residue in a sprinkler-irrigated corn system in Colorado.
165 - Sarah I. Leichty
Does residue placement affect soil carbon dynamics in irrigated corn?
Keywords: carbon sequestration